The approach of general practitioners in Lagos to the detection and evaluation of hypertension - Ale, Olagoke Korede (Clin Hypertens, 2015)
INTRODUCTION: Hypertension (HTN) control is a major public health and clinical challenge. A number of guidelines exist globally to assist in tackling this challenge. The aim of this study was to determine conformity of the HTN detection and evaluation practices of a sample of Lagos-based general practitioners (GPs) to international guidelines. METHODS: Self-administered structured questionnaires were used to collect data from a cohort of GPs attending continuing medical education programs in Lagos. RESULTS: Out of the 460 GPs that were approached, 435 agreed to participate in the study, with questionnaires from 403 GPs analyzed. The average age and number of years post-registration of the GPs were 40.0 ± 11.3 years and 14.3 ± 11.1 years, respectively. Two thirds (n = 269) were in private practice. Their daily average total and HTN patients’ loads were 17.4 ± 14.3 and 4.4 ± 3.5, respectively. Awareness of HTN guidelines was 46.7% (n = 188), while 18.1% (n = 73) was able to name one or more HTN guidelines. The approaches of these GPs to the detection and evaluation of HTN and their relationships to the GPs’ experience were heterogeneous. DISCUSSION: The approach of the GPs to detection and evaluation of HTN though heterogeneous is unsatisfactory and may partly contribute to poor HTN control in Nigeria. Strengthening the capacity of GPs in this regard through continuous medical education may greatly improve HTN control.